Calcium carbonate deposits and microbial assemblages on microplastics in oligotrophic freshwaters. (March 2021) - Kniggendorf, Ann-Kathrin; Nogueira, Regina; Lorey, Corinna; Roth, Bernhard
Abstract: Microplastics are solid polymer particles with a wide variety of surface properties, found in most waterbodies, and known as carriers of distinct microbial communities affecting the fate of the particles in the environment. Little is known about the formation of mineral deposits on microplastics and how these deposits connect to microbial assemblages and affect the physicochemical properties of the particles. In addition, most of the available research on this topic is based on large microplastics with sizes between 100 μm and up to 5 mm, rather than the small microplastics often found in drinking water sources. To narrow this gap in our understanding of environmental effects on small microplastics, two types of small microplastics made of two distinct polymers, poly(methyl methacrylate) (PMMA) and poly(tetrafluoroethylene) (PTFE) with sizes ranging from 15 to 150 μm, were incubated for six months in unprocessed and processed drinking water with increasing ionic concentration to allow for the formation of mineral deposits and microbial assemblages. Spatially resolved analysis with fluorescent in situ hybridization and confocal Raman microscopic imaging revealed deposits of calcium carbonates and scattered microbial assemblages on all microplastics, with structure, extend, and microbial association with the carbonates depending on the respective microplastic. Notably, PTFE floatation was overcome after three months in unprocessed drinking water but remained unchanged in processed drinking water, whereas PMMA appeared unaffected, indicating that the fate of microplastics in the environment may depend on polymer type and the encountered aquatic conditions forming mineral and microbial attachments to the particle surface. Graphical abstract: Image 1 Highlights: Calcium carbonate precipitates as microcrystals on PMMA and PTFE. Calcium carbonates also appear as sheets and flocs on PTFE. Microbial assemblages are only attached to precipitated calcium carbonate on PTFE. Microbial assemblages are directly attached to the polymer surface on PMMA.